Effect of rebonding and bleaching on ion release and electron microscope views of spherical and admixed amalgams - Horieh Mousavi; Hamideh Mohammadipour; Azadeh Gholami (Isfahan University of Medical Sciences, 2013)
AbstractIntroduction: During application of bleaching materials, they may come into contact with existing amalgam restorations resulting in changes in amalgam structure. The aim of the present study was to evaluate the influence of rebonding and bleaching on the release of metallic ions and microstractures of admixed and spherical amalgams.Materials and Methods: This experimental in vitro study was performed on 96 Class V cavities (3.5 mm in length, 2 mm in width and depth) prepared on sound human premolars and restored with amalgams containing spherical and admixed particles. In half of the samples of each amalgam type rebonding procedure was carried out with Scotchbond Multi-purpose adhesive system and Guardian Seal resin sealant. Then half of the amalgam restorations, with or without rebonding, were exposed to 30% carbamide peroxide (n = 12). The amount of metallic ions released from amalgams was determined by atomic absorption spectrometry. Surface topography and compositions of two samples in each group were observed under a scanning electron microscope (SEM). Data were analyzed by t-test and multivariate ANOVA (α = 0.05). Results: 30% carbamide peroxide gel caused a significant increase in Hg released from amalgams in non-rebonded groups (p value < 0.001). There was no significant difference in ion release from spherical and admixed amalgams (p value = 0.73). Rebonding resulted in significant reduction in Hg release (p value = 0.007). Conclusion: Exposure of spherical and admixed amalgams to 30% carbamide peroxide gel, without rebonding, caused a significant increase in Hg release from amalgam and changed amalgam microstructure. Key words: Bleaching, Dental amalgam, Mercury, Silver